A comparison of microRNA sequencing reproducibility and noise reduction using mirVana and TRIzol isolation methods. (1st January 2014) - Guo, Yan; Bosompem, Amma; Zhong, Xue; Clark, Travis; Shyr, Yu; Kim, Annette S.
MicroRNAseq (miRNAseq) is a form of RNAseq technology that has become an increasingly popular alternative to miRNA expression profiling. Unlike messenger RNA (mRNA), miRNA extraction can be difficult, and sequencing such small RNA can also be problematic. We designed a study to test the reproducibility of miRNAseq technology and the performance of the two popular miRNA isolation methods, mirVana and TRIzol, by sequencing replicated samples using microRNA isolated with each kit. Through careful analysis of our data, we found excellent repeatability of miRNAseq technology. The mirVana method performed better than TRIzol in terms of useful reads sequenced, number of miRNA identified, and reproducibility. Finally, we identified a baseline noise level for miRNAseq technology; this baseline noise level can be used as a filter in future miRNAseq studies.